Allosteric modulation as a unifying mechanism for receptor function and regulation1. (September 2017) - Changeux, Jean‐Pierre; Christopoulos, Arthur
Abstract : Four major receptor families enable cells to respond to chemical and physical signals from their proximal environment. The ligand‐ and voltage‐gated ion channels, G‐protein‐coupled receptors, nuclear hormone receptors and receptor tyrosine kinases are all allosteric proteins that carry multiple, spatially distinct, yet conformationally linked ligand‐binding sites. Recent studies point to common mechanisms governing the allosteric transitions of these receptors, including the impact of oligomerization, pre‐existing and functionally distinct conformational ensembles, intrinsically disordered regions, and the occurrence of allosteric modulatory sites. Importantly, synthetic allosteric modulators are being discovered for these receptors, providing an enriched, yet challenging, landscape for novel therapeutics.